Validity and Reliability Test of Child Anxiety Instrument (SCARED) on Students of Sekolah Dasar Kedungsari 5 Magelang - Stri Nareswari; Budi Pratiti; Sumarni (Community Medicine and Education Journal, 2022)
Anxiety disorders rank the 9th cause of DALYs, which can have long-term effects. The COVID-19 pandemic can trigger anxiety disorders in children related to changes in learning, habituation of new behaviors, COVID-19 disease itself, and other factors. Detection of anxiety disorders in children needs to be done early so that it can avoid its long-term effects. Screen for Children Anxiety Related Emotion Disorder (SCARED) is a multi-informant instrument that is considered good for screening anxiety disorders in children, so it is necessary to assess its validity and reliability so that it can be used in Indonesia. This study aimed to test the validity and reliability SCARED instrument in Indonesian to measure the tendency of children's Anxiety Disorders. This study was an observational study with a cross-sectional design. Subjects were students of Sekolah Dasar Negeri Kedungsari 5 Magelang (n=220). Content validity test using Pearson product-moment and construct validity test using CFA. Concurrent test with RCMAS using Pearson correlation. Reliability test by calculating the value of Cronbach alpha. The result content validity test showed that all children's versions of SCARED items and parents' versions of SCARED had r counts above r tables. There was concern with the RCMAS and the SCARED children version concurrent with the parent version. Cronbach's alpha value of SCARED child version 0.901 and parent version 0.891. The Indonesian version of SCARED is a valid and reliable instrument to assess the tendency of children's anxiety disorders in elementary school students.